IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION IN COMMUNITY SOCIAL LIFE: A STUDY ON THE INTEGRATION OF RELIGIOUS VALUES AND LOCAL WISDOM - Halimah, Nur; Fahri, Ismail; Hasanah, Neneng; Thontawi, M; Widoyono, Agil (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
This study aims to analyze the implementation of Islamic Religious Education (IRE) in community social life as an effort to shape attitudes and behaviors based on humanistic values. It also examines the integration of Islamic religious values with local wisdom within the community, enabling IRE to strengthen harmonious social relationships, mutual respect, and collective well-being. In this study, IRE is understood not merely as a formal learning process but as a humanizing space where Islamic values are instilled and lived through everyday social practices, such as respect, justice, care, and social responsibility. The research employs a qualitative descriptive approach, focusing on a deep understanding of social realities and human experiences in the studied context. Data were collected through observation, in-depth interviews with religious and community leaders, and documentation, to comprehensively capture social realities and understand the experiences, values, and meanings embedded in community life. Data analysis was conducted through stages of data reduction, presentation, and thematic conclusion drawing to identify patterns of meaning, values, and human dynamics. The findings indicate that IRE is manifested in socio-religious activities integrated with local wisdom, such as mutual cooperation, deliberation, adat-based religious events, and social care practices that foster solidarity, togetherness, and mutual respect. The integration of religious values and local wisdom plays a crucial role in building social harmony, strengthening inter-community solidarity, and sustaining Islamic values in a culturally meaningful way. The study concludes that IRE integrated with local wisdom is an effective approach to developing a religious, inclusive, and humanistic community life deeply rooted in local culture.